Turkish Parties’ Positions towards the EU: between Europhilia and Europhobia - Mehmet Bardakçı (Romanian Journal of European Affairs, 2010)
This research is a case study meant to find out whether the arguments put forward by Szczerbiak and Taggart analyzing Euroscepticism in the party systems of the EU candidate states of Central and Eastern Europe hold true for party-based Euroscepticism in Turkish politics. The primary argument of this article is that the Turkish party system displays many similarities with its Central and Eastern European counterparts despite some differences. In order to test this argument, firstly the nature of Euroscepticism in Turkey and Turkish political parties is clarified. Then, the characteristics of Euroscepticism in Turkish political parties are tested against Szczerbiak and Taggart’s hypotheses with respect to the Central and Eastern European candidate countries. Among the propositions tested are the influence of a party’s position in the left-right spectrum on the expression of Euroscepticism, the relationship between the level of public Euroscepticism and the level of Euroscepticism in the party-system, the variation between soft-Euroscepticism and hard-Euroscepticism in the candidate and member states of the EU, the correlation between the level of Euroscepticism and the prospect for EU membership, the link between state development and the level of party-based Euroscepticism, and the relationship between public Euroscepticism and party-based Euroscepticism.